Effect of increasing energy cost on arm coordination at different exercise intensities in elite sprint swimmers - Komar, J.; Lepretre, P.-M.; Alberty, M.; Vantorre, J.; Fernandes, R. J.; Hellard, P.; Chollet, D.; Seifert, L. (Biomechanics and Medicine in Swimming XI, 2010)
The purpose of this study was to analyze the changes of the stroking parameters and the coordination induced by the increase of energy cost (C) of aquatic locomotion. Six elite sprint swimmers performed a 6.300-m incremental swimming test. Stroking parameters (stroke rate, SR; stroke length, SL) and arm coordination (measured by index of coordination, IdC) have been calculated from video data and the C by measuring oxygen consumption and blood lactate. Results showed that an increase in C led to significant increases in IdC, SR and a decrease in SL. Linear regression between IdC and C, SR and C and SL and C suggested that a specific C corresponds to the emergence of a specific coordination and SR/SL ratio. The increase of the anaerobic part of C suggested that fatigue could also influence the emergence of motor organization.